Viabilitas Serbuk Sari dan Keberhasilan Persilangan antara Durian Montong dan Sitokong pada Tiga Waktu Berbeda - Zulfahmi, Zulfahmi; Batubara, Riyo Syahputra; Rosmaina, Rosmaina (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
The success of durian pollination in nature is very low (<5%) due to high self-incompatibility in durian flowers. Artificial cross-pollination is an alternative method that can be used to increase the successful pollination of durian. So, information on the pollen viability of the durian flower and the time of artificial cross-pollination accurate and effective is required. This research aimed to examine the pollen viability of the durian varieties of Montong and Sitokong varieties at three different times and to determine the success rate of artificial cross-pollination between both varieties at three different times. This research was carried out at the Morpoyan Seed Center and the Genetic and Breeding Laboratory of the Faculty of Agriculture, UIN Suska Riau. Pollen viability testing used the staining method. Artificial cross-pollination between the Montong durian and the Sitokong durian was carried out reciprocally at three different times (11.00–13.00, 15.00–17.00, and 19.00–21.00). The total number of flowers crossed was 300. The results of this study showed that the percentage of pollen viability of Montong durian at 11.00–13.00, 15.00–17.00, and 19.00–21.00 was 94.91, 97.67, and 97.23%, respectively. While the pollen viability of Sitokong durian was 93.33% at 11.00–13.00, 94.45% at 15.00–17.00, and 94.76% at 19.00–21.00. The successful rate of crosses of durian Montong (♀) x Sitokong (♂) at 11.00–13.00, 15.00–17.00, and 19.00–21.00, respectively were 46, 26, and 34%, while the percentage of success of durian Sitokong crosses (♀) x Montong (♂) is 48% at 11.00–13.00, 54% at 15.00–17.00, and 22% at 19.00–21.00. Successful artificial cross-pollination between Montong and Sitokong durian or vice versa was higher at 11.00–13.00 compared to other times. The results of this study can be utilized to formulate the timing of artificial cross-pollination of durian in the future.